Early hydration and microstructure formation of Portland cement paste studied by oscillation rheology, isothermal calorimetry, 1H NMR relaxometry, conductance and SAXS. (April 2020) - Bogner, A.; Link, J.; Baum, M.; Mahlbacher, M.; Gil-Diaz, T.; Lützenkirchen, J.; Sowoidnich, T.; Heberling, F.; Schäfer, T.; Ludwig, H.-M.; Dehn, F.; Müller, H.S.; et al.
Abstract: An open question in predicting the rheological properties of cement suspensions has been whether changes of rheology during hydration are merely a result of shifts in the electrostatic interaction patterns of the particles over time, or whether and to which extent steric bridging by hydration products occurs. The latter could explain phenomena such as thixotropy. In this context, parallel investigations using both rheological tests and isothermal calorimetry, 1 H NMR relaxometry, conductance and small-angle X-ray scattering (SAXS) measurments were carried out. It could be shown that as early as approx. 2.5 h after water addition at approx. 30 °C, small amounts of Calcium Silicate Hydrate (C-S-H) form which may contribute to a bridging of the cement particles. This phase is followed by rapid C-S-H formation, leading to a non-linear increase in paste stiffness. This phase ends with percolation, i.e. the paste stiffness increases dramatically, simultaneously with the formation of gel pore like structures, which could be observed using NMR.